Fortalecimiento del suelo pelvico con electroterapia en pacientes post’parto que acuden al Hospital Dr.publio Escobar Gomez de la Torre - Díaz Echeverría, Johanna Jenelle (2017)
The pelvic floor is the set of muscles and tendons that close the lower abdominal cavity, while retaining and conserving the bladder, uterus and rectum in their normal position. Physiotherapy as a branch of medicine, is responsible for preventing and readapting the general conditions of the human body, and one of the specialties is the study and treatment of conditions of the pelvic floor musculature through the application of physical agents in This case electrotherapy, whose purpose is to rehabilitate the muscles of the pelvic floor as a non-invasive therapeutic solution and no conflict for the patient. The proposal of strengthening the pelvic floor through the application of electrotherapy in a postpartum patient of the Hospital Publio Escobar Gómez de la Torre, guides the quantitative-qualitative study of electrostimulation that determine the guidelines and guidelines that allow to reach optimally the recovery of the Pelvic floor to prevent future complications in postpartum women who have weakness in their muscles. The population in this investigation consisted of 20 patients, it was demonstrated that electrotherapy has both preventive and curative advantages in postpartum patients who may present complications secondary to weakening pelvic floor, and it is recommended to implement this technique in postpartum patients